The Italian preparticipation evaluation programme: diagnostic yield, rate of disqualification and cost analysis. Issue 4 (17th July 2019) - Vessella, Teresina; Zorzi, Alessandro; Merlo, Laura; Pegoraro, Cinzia; Giorgiano, Flaviano; Trevisanato, Michele; Viel, Mirella; Formentini, Pietro; Corrado, Domenico; Sarto, Patrizio
Abstract : Introduction: Italian law mandates that every competitive athlete must undergo annual preparticipation evaluation (PPE) to identify cardiovascular (CV) diseases that pose a risk of sudden death (SD) during sport and other conditions that may threaten the athlete's health. We investigated the diagnostic yield, rate of disqualification and costs of our PPE. Methods: We included 5910 consecutive apparently healthy athletes (61% males, mean age 15±4 years) who underwent annual PPE performed by a sports medicine specialist. The PPE included history, physical examination, weight, height and blood pressure measurement, test of visual acuity, spirometry, urine chemistry, resting 12-lead ECG and exercise testing with ECG monitoring. In cases of abnormal findings, we carried out second-line investigations. Results: During a 12-month study period, 5.326 (90.2%) athletes were cleared for competition after a normal first-line evaluation and 584 (9.8%) underwent one or more further examinations. Of those, 88 (1.5%) were diagnosed to have a CV disease (including 18 (0.3%) at-risk of SD) and 31 (0.5%) had a non-CV diagnosis. A total of 32 (0.5%) athletes were temporarily (n=15) or permanently (n=17) disqualified from competitive sports. The average cost per athlete was €79, which consisted of €64 (80%) for first-line evaluations and €15 (20%) for additional investigations. Conclusion: PPE according to the Italian model identified a range of diseases in 2.0% of apparently healthy athletes at an average cost of €79.